2017
DOI: 10.1139/cjz-2016-0198
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ovarian maturation throughout the reproductive cycle of the Neotropical cichlid fishCichlasomadimerus(Teleostei, Cichliformes)

Abstract: In this study, we analyzed gene expression profiles, plasma steroids concentrations, and gonadal morphology throughout the reproductive cycle of female Cichlasoma dimerus (Heckel, 1840), a monogamous cichlid fish exhibiting social hierarchies. Fish were analyzed at six phases encompassing their annual cycle, namely resting (during the nonreproductive period), prespawning, 30 h post spawning, 4 days post spawning, 10 days post spawning, and subordinate (during the reproductive period). The histological and hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
3
3
0
Order By: Relevance
“…Thus the first objective of the present study was to assess the relationship between GSI and baseline vtg and erα expression in female fathead minnows. The positive, significant correlations between GSI and vtg and erα expression identified in present study suggest that GSI influences the baseline expression of estrogen‐responsive genes, congruent with the relationship previously shown in the literature (Panprommin et al ; Nagler et al ; Tingaud‐Sequeira et al ; Varela et al ). Because exposures to anti‐estrogens and nonaromatizable androgens typically lead to decreases in hepatic expression of vtg and erα in female fish (Villeneuve et al ; Zhang et al ; Dorts et al ; Sun et al ), it is reasonable to expect that differences in female GSI values may influence the magnitude of vtg and erα down‐regulation following exposures to anti‐estrogens and nonaromatizable androgens.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus the first objective of the present study was to assess the relationship between GSI and baseline vtg and erα expression in female fathead minnows. The positive, significant correlations between GSI and vtg and erα expression identified in present study suggest that GSI influences the baseline expression of estrogen‐responsive genes, congruent with the relationship previously shown in the literature (Panprommin et al ; Nagler et al ; Tingaud‐Sequeira et al ; Varela et al ). Because exposures to anti‐estrogens and nonaromatizable androgens typically lead to decreases in hepatic expression of vtg and erα in female fish (Villeneuve et al ; Zhang et al ; Dorts et al ; Sun et al ), it is reasonable to expect that differences in female GSI values may influence the magnitude of vtg and erα down‐regulation following exposures to anti‐estrogens and nonaromatizable androgens.…”
Section: Discussionsupporting
confidence: 92%
“…The hypothesis that the reproductive status of an organism can influence their response to REDC exposure is based on previous evidence across multiple teleost species showing that reproductive status, as assessed via a variety of different metrics including GSI, is associated with baseline vtg and erα expression (Funkenstein et al ; Burki et al ; Panprommin et al ; Pousis et al ; Nagler et al ; Tingaud‐Sequeira et al ; Varela et al ). Thus the first objective of the present study was to assess the relationship between GSI and baseline vtg and erα expression in female fathead minnows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resumption of the meiotic process initiates the maturation stage (Abascal & Medina, 2005), which is completed with fertilization (Quagio-Grassiotto et al ., 2013). In this stage, the germ vesicle (nucleus) migrates towards the micropyle region (Honji et al ., 2006; Quagio-Grassiotto et al ., 2011; Cassel et al ., 2017a; Varela et al ., 2017), as observed for D. aequipinnatus . However, for D. aequipinnatus , the presence of lipid droplets was not observed.…”
Section: Discussionsupporting
confidence: 70%
“…Stain: haematoxylin and eosin. Quagio-Grassiotto et al, 2011;Cassel et al, 2017a;Varela et al, 2017), as observed for D. aequipinnatus. However, for D. aequipinnatus, the presence of lipid droplets was not observed.…”
Section: Discussionsupporting
confidence: 64%